2018
DOI: 10.4186/ej.2018.22.5.31
|View full text |Cite
|
Sign up to set email alerts
|

Lipids from Vitellaria paradoxa Gaertn Seeds by Supercritical CO2: Extraction and Optimization of Parameters by Response Surface Methodology

Abstract: Supercritical carbon dioxide (CO2) was employed to extract lipids from Vitellaria paradoxa Gaertn seeds in semi-batch process at various operating conditions to optimize extraction process. The extraction processes were carried out at 40-60 o C and 20-40 MPa with 2-4 ml min-1 CO2 flow rates. Analysis of variance (ANOVA) with 33 factorial design combined with statistical was used to optimize variables in the process of Vitellaria paradoxa Gaertn seeds lipids extraction with supercritical CO2. The FT-IR spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Supercritical CO 2 (SC-CO 2 ) is the most commonly used extraction solvent for supercritical fluid extraction and is neither toxic nor flammable. It exhibits selectivity because of its low viscosity, high diffusivity, and density between that of a liquid and a gas [1][2][3][4]. SC-CO 2 is suitable for the extraction of non-polar substances; for example, vegetable neutral lipids such as C16:0, C18:0, C18:1, and C18:2 have been selectively extracted from Vitellaria paradoxa Gaertn seeds [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supercritical CO 2 (SC-CO 2 ) is the most commonly used extraction solvent for supercritical fluid extraction and is neither toxic nor flammable. It exhibits selectivity because of its low viscosity, high diffusivity, and density between that of a liquid and a gas [1][2][3][4]. SC-CO 2 is suitable for the extraction of non-polar substances; for example, vegetable neutral lipids such as C16:0, C18:0, C18:1, and C18:2 have been selectively extracted from Vitellaria paradoxa Gaertn seeds [2].…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits selectivity because of its low viscosity, high diffusivity, and density between that of a liquid and a gas [1][2][3][4]. SC-CO 2 is suitable for the extraction of non-polar substances; for example, vegetable neutral lipids such as C16:0, C18:0, C18:1, and C18:2 have been selectively extracted from Vitellaria paradoxa Gaertn seeds [2]. These studies have shown that the higher the operating pressure of SC-CO 2 , the higher the extracted amounts, and such studies have been carried out at a maximum pressure of 40 MPa, although this is dependent on the mechanical strength of the equipment required for experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation